ANALISIS MINAT BELAJAR SISWA TERHADAP MATEMATIKA PADA SEKOLAH BERBASIS PONDOK PESANTREN DI MADRASAH TSANAWIYAH - Umi Hanifah; Faiqoh (Universitas Nahdlatul Ulama Pasuruan, 2023)
Mathematics has a significant influence on the development of technology andscience. Both of these fields use mathematics as a tool for further study. At the same time, mathematics influences science and technology by creating new theories and methods(Siagian, 2016). Math is important for many other subjects, including science and technology. It is important to understand other subjects as it requires critical thinking and decision making. Students must learn the material before they can negotiate its use in theirreasoning and decisions. In an effort the researcher wants to increase the title of the problem and research into a specific subject. The reason is because he has analyzed thisproblem from the same background